Spectrometer for detailed study of radon and thoron system decay products - Frolov, O.S.; Sadovnichy, A.A.; Pavlenko, Yu.N.; Shevchenko, V.A.; Zaytsevsky, I.L.; Podviyaniuk, R.B.; Pavlenko, I.O. (Вопросы атомной науки и техники, 2004)
The results of development of an aspiration type spectrometer for investigation of daughter products of radon
and thoron are presented. Main parameters of the device: active detector area of 32 cm2, air pumping through the filter up to 100 liters/min, energy resolution of the detection unit of 50…70 keV. Measurements are made both during
the pumping and after the pumping. Accumulation, processing, representation and storage of data are made using a
personal computer incorporated into the device. Setup and control of the device are made on the computer keyboard.
The results of measurements of spectra of the radon and thoron system, including dependencies of α-activity of various radio-nuclides are shown. With this device it’s also possible to measure electron energy loss spectra. Представлено результати розробки спектрометра аспіраційного типу для дослідження дочірніх
продуктів розпаду радону і торону. Основні параметри приладу: активна площа детектора 32 см2, швидкість
продувки повітря через фільтр – до 100 л/хв, енергетична роздільна здатність блоку детектування 50…
70 кеВ. Виміри проводяться як після продувки повітря через фільтр, так і під час продувки. До складу
приладу входить персональний комп'ютер, за допомогою якого виконуються набір, обробка, представлення і
збереження даних. Настроювання і керування вимірами здійснюються з клавіатури комп'ютера. Приведено
результати вимірів спектрів системи радону і торону, у тому числі кінетичні залежності α-активності різних
радіонуклідів. Прилад дає можливість вимірювати також спектри енергетичних втрат електронів. Представлены результаты разработки спектрометра аспирационного типа для исследования дочерних
продуктов распада радона и торона. Основные параметры прибора: активная площадь детектора 32 см2, скорость продувки воздуха через фильтр – до 100 л/мин, энергетическое разрешение блока детектирования
50…70 кэВ. Измерения проводятся как после продувки воздуха через фильтр, так и во время продувки. В состав прибора входит персональный компьютер, с помощью которого производится набор, обработка, представление и хранение данных. Настройки и управление измерениями осуществляются с клавиатуры
компьютера. Приведены результаты измерений спектров системы радона и торона, в том числе кинетические зависимости α-активности различных радионуклидов. Прибор дает возможность измерять также спектры энергетических потерь электронов.